Technological advances for analyzing the content of organ-on-a-chip by mass spectrometry - Hadavi, Darya; Tosheva, Ilona; Siegel, Tiffany Porta; Cuypers, Eva; Honing, Maarten (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Three-dimensional (3D) cell cultures, including organ-on-a-chip (OOC) devices, offer the possibility to mimic human physiology conditions better than 2D models. The OOC devices have a wide range of applications, including mechanical studies, functional validation, and toxicology investigations. Despite many advances in this field, the major challenge with the use of OOCs relies on the lack of online analysis methods preventing the real-time observation of cultured cells. Mass spectrometry is a promising analytical technique for real-time analysis of cell excretes from OOC models. This is due to its high sensitivity, selectivity, and ability to tentatively identify a large variety of unknown compounds, ranging from metabolites, lipids, and peptides to proteins. However, the hyphenation of OOC with MS is largely hampered by the nature of the media used, and the presence of nonvolatile buffers. This in turn stalls the straightforward and online connection of OOC outlet to MS. To overcome this challenge, multiple advances have been made to pre-treat samples right after OOC and just before MS. In this review, we summarised these technological advances and exhaustively evaluated their benefits and shortcomings for successful hyphenation of OOC with MS.